2021
DOI: 10.1002/cam4.3817
|View full text |Cite
|
Sign up to set email alerts
|

Sputum cell‐free DNA: Valued surrogate sample for the detection of EGFR exon 20 p.T790M mutation in patients with advanced lung adenocarcinoma and acquired resistance to EGFR‐TKIs

Abstract: BackgroundSputum cell‐free DNA (cfDNA) is a valuable surrogate sample for assessing EGFR‐sensitizing mutations in patients with advanced lung adenocarcinoma. Detecting EGFR exon 20 p.T790 M (p.T790 M) is much more challenging due to its limited availability in tumor tissues. Exploring sputum cfDNA as an alternative for liquid‐based sample type in detecting p.T790 M requires potential improvement in clinical practice.MethodsA total of 34 patients with EGFR‐sensitive mutation‐positive lung adenocarcinoma and acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 29 publications
2
29
1
Order By: Relevance
“…As a consequence, in this study, a “positive bronchus sign” was no prerequisite to find ctDNA in the sputum. Our results confirm earlier studies that sputum is a useful specimen for EGFR mutation analysis, 20-23 but also show that ddPCR is able to detect ctDNA in sputum samples, although cytological examinations do not identify cancer cells in the specimens. This finding is an important milestone to support further studies on the use of sputum for other molecular targets in NSCLC and, most likely, even beyond.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As a consequence, in this study, a “positive bronchus sign” was no prerequisite to find ctDNA in the sputum. Our results confirm earlier studies that sputum is a useful specimen for EGFR mutation analysis, 20-23 but also show that ddPCR is able to detect ctDNA in sputum samples, although cytological examinations do not identify cancer cells in the specimens. This finding is an important milestone to support further studies on the use of sputum for other molecular targets in NSCLC and, most likely, even beyond.…”
Section: Discussionsupporting
confidence: 91%
“…They reported that sputum results matched in 46.2% with confirmed EGFR mutations in tumor samples among the 65 included patients. 22 To improve the detection rate of EGFR , Wu et al combined plasma, sputum, and urine samples and used a next-generation-sequencing platform in 50 patients. They reported a combined sensitivity of 91%, with 84% in plasma and 63% in sputum.…”
Section: Introductionmentioning
confidence: 99%
“…In ascites fluid from a cohort of mixed KRAS-positive and wild-type tumours, KRAS mutations were detected in 100% of the KRAS-positive cohort, and in an additional 19% of tumours deemed wild-type by tissue biopsy [ 34 ]. Sputum and saliva, however, though similarly representative of tumour tissue, are less sensitive sources for cfDNA analysis [ 17 , 35 ].…”
Section: Reliable Molecular Profiling Of Diseasementioning
confidence: 99%
“…Improved ctDNA detection rates have been observed in cfDNA from non-blood sources compared to blood [ 29 ], with the exception of saliva [ 35 ] and sputum [ 17 , 38 ]. This has been repeatedly demonstrated in pleural effusions secondary to lung cancer, with an increased sensitivity to EGFR mutations in malignant pleural effusions over plasma, as well as over cell pellets from the effusions [ 31 , 32 , 33 , 36 ].…”
Section: Reliable Molecular Profiling Of Diseasementioning
confidence: 99%
See 1 more Smart Citation